Shikonin-loaded antibody-armed nanoparticles for targeted therapy of ovarian cancer - Matthaiou EI (Dove Medical Press, 2014)
Efthymia-Iliana Matthaiou,1,2 Jaleh Barar,1,3 Raphael Sandaltzopoulos,2 Chunsheng Li,1 George Coukos,1,4 Yadollah Omidi1,3 1Ovarian Cancer Research Center, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, USA; 2Department of Molecular Biology and Genetics, Democritus University of Thrace, Alexandroupolis, Greece; 3Research Center for Pharmaceutical Nanotechnology, Faculty of Pharmacy, Tabriz University of Medical Sciences, Tabriz, Iran; 4Ludwig Institute for Cancer Research, University of Lausanne, Lausanne, Switzerland Abstract: Conventional chemotherapy of ovarian cancer often fails because of initiation of drug resistance and/or side effects and trace of untouched remaining cancerous cells. This highlights an urgent need for advanced targeted therapies for effective remediation of the disease using a cytotoxic agent with immunomodulatory effects, such as shikonin (SHK). Based on preliminary experiments, we found SHK to be profoundly toxic in ovarian epithelial cancer cells (OVCAR-5 and ID8 cells) as well as in normal ovarian IOSE-398 cells, endothelial MS1 cells, and lymphocytes. To limit its cytotoxic impact solely to tumor cells within the tumor microenvironment (TME), we aimed to engineer SHK as polymeric nanoparticles (NPs) with targeting moiety toward tumor microvasculature. To this end, using single/double emulsion solvent evaporation/diffusion technique with sonication, we formulated biodegradable NPs of poly(lactic-co-glycolic acid) (PLGA) loaded with SHK. The surface of NPs was further decorated with solubilizing agent polyethylene glycol (PEG) and tumor endothelial marker 1 (TEM1)/endosialin-targeting antibody (Ab) through carbodiimide/N-hydroxysuccinimide chemistry. Having characterized the physicochemical and morphological properties of NPs, we studied their drug-release profiles using various kinetic models. The biological impact of NPs was also evaluated in tumor-associated endothelial MS1 cells, primary lymphocytes, and epithelial ovarian cancer OVCAR-5 cells. Based on particle size analysis and electron microscopy, the engineered NPs showed a smooth spherical shape with size range of 120 to 250 nm and zeta potential value of -30 to -40 mV. Drug entrapment efficiency was ~80%–90%, which was reduced to ~50%–60% upon surface decoration with PEG and Ab. The liberation of SHK from NPs showed a sustained-release profile that was best fitted with Wagner log-probability model. Fluorescence microscopy and flow cytometry analysis showed active interaction of Ab-armed NPs with TEM1-positive MS1 cells, but not with TEM1-negative MS1 cells. While exposure of the PEGylated NPs for 2 hours was not toxic to lymphocytes, long-term exposure of the Ab-armed and PEGylated NPs was significantly toxic to TEM1-positive MS1 cells and OVCAR-5 cells. Based on these findings, we propose SHK-loaded Ab-armed PEGylated PLGA NPs as a novel nanomedicine for targeted therapy of solid tumors. Keywords: nanomedicine, nanoparticle, ovarian cancer, shikonin, targeted therapy, tumor vasculature